2003
DOI: 10.1210/jc.2002-021434
|View full text |Cite
|
Sign up to set email alerts
|

Different Basic Fibroblast Growth Factor and Fibroblast Growth Factor-Antisense Expression in Eutopic Endometrial Stromal Cells Derived from Women with and without Endometriosis

Abstract: In all species studied, the basic fibroblast growth factor (bFGF) gene is transcribed into multiple mRNAs, one of which is an antisense RNA (1B FGF-AS) probably involved in regulating the stability of the sense transcript. In this study we investigated whether the regulatory mechanisms of bFGF expression might be altered in endometrial stromal cells derived from women with endometriosis. bFGF and 1B FGF-AS mRNA levels were quantified in primary cultures of eutopic endometrial stromal cells derived from 29 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…We refer to this phenomenon as antisensecorrelated splicing. Although a few examples of antisense-correlated splicing events have been reported in the literature (Hastings et al 1997;Mihalich et al 2003;Yan et al 2005;Annilo et al 2009), we provide for the first time evidence linking antisense transcription to alternative splicing across the majority of SAS loci expressed in human lymphoblastoid cell lines.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We refer to this phenomenon as antisensecorrelated splicing. Although a few examples of antisense-correlated splicing events have been reported in the literature (Hastings et al 1997;Mihalich et al 2003;Yan et al 2005;Annilo et al 2009), we provide for the first time evidence linking antisense transcription to alternative splicing across the majority of SAS loci expressed in human lymphoblastoid cell lines.…”
Section: Discussionmentioning
confidence: 62%
“…In a limited number of cases, antisense transcription has been correlated to sense gene splicing (Mihalich et al 2003;Louro et al 2007;Annilo et al 2009) or shown to regulate sense gene splicing (Krystal et al 1990;Kuersten and Goodwin 2003;Yan et al 2005;Beltran et al 2008;Allo et al 2009). One well-characterized example is antisense-mediated splicing regulation of the thyroid hormone receptor THRA by the antisense transcript NR1D1 (Hastings et al 1997).…”
mentioning
confidence: 99%
“…The sense-encoded protein induces growth, differentiation and antiapoptotic behavior; over expression of FGF-2 is linked to tumor progression and ectopic cell proliferation. 30 The FGF-related antisense transcript was first identified in Xenopus oocytes. Interestingly, Kimelman and Kirschner found that the sense and the antisense transcript were edited in the overlapping region suggesting that the two transcripts hybridized.…”
Section: Natural Antisense Transcripts In Focusmentioning
confidence: 99%
“…Interestingly, Kimelman and Kirschner found that the sense and the antisense transcript were edited in the overlapping region suggesting that the two transcripts hybridized. [30][31][32] Subsequently the antisense transcript was cloned from various species including chick, rat and human. 16,33,34 Sense and antisense transcripts overlap tail to tail in the 3' non-coding region, only the Xenopus antisense transcript reaches into the open reading frame of the sense transcript.…”
Section: Natural Antisense Transcripts In Focusmentioning
confidence: 99%
See 1 more Smart Citation